Additive Manufacturing of Nerve Decellularized Extracellular Matrix-Contained Polyurethane Conduits for Peripheral Nerve Regeneration - Chen, Yi-Wen (Polymers (Basel), 2019)
The nervous system is the part of our body that plays critical roles in the coordination of actions and sensory information as well as communication between different body parts through electrical signal transmissions. Current studies have shown that patients are likely to experience a functional loss if they have to go through a nerve repair for >15 mm lesion. The ideal treatment methodology is autologous nerve transplant, but numerous problems lie in this treatment method, such as lack of harvesting sites. Therefore, researchers are attempting to fabricate alternatives for nerve regeneration, and nerve conduit is one of the potential alternatives for nerve regeneration. In this study, we fabricated polyurethane/polydopamine/extracellular matrix (PU/PDA/ECM) nerve conduits using digital light processing (DLP) technology and assessed for its physical properties, biodegradability, cytocompatibility, neural related growth factor, and proteins secretion and expression and its potential in allowing cellular adhesion and proliferation. It was reported that PU/PDA/ECM nerve conduits were more hydrophilic and allowed enhanced cellular adhesion, proliferation, expression, and secretion of neural-related proteins (collagen I and laminin) and also enhanced expression of neurogenic proteins, such as nestin and microtubule-associated protein 2 (MAP2). In addition, PU/PDA/ECM nerve conduits were reported to be non-cytotoxic, had sustained biodegradability, and had similar physical characteristics as PU conduits. Therefore, we believed that PU/PDA/ECM nerve conduits could be a potential candidate for future nerve-related research or clinical applications.